A Quality Improvement Project Measuring the Effect of an Evidence-Based Civility Training Program on Nursing Workplace Incivility in a Rural Hospital Using Quantitative Methods - Nancy Elizabeth Armstrong (Online Journal of Rural Nursing and Health Care, 2017)
Workplace incivility is a well-documented issue in nursing.  It has the potential to cause emotional and physical distress in victims, and potentially affect the quality of care provided. Research in acute care settings found that facilitated educational training sessions related to workplace incivility, in combination with experiential learning activities, assisted nurses in improving their understanding of workplace incivility and their communication skills.  It has also been found to reduce workplace incivility.  The purpose of this quality improvement project was to see if implementation of a civility training program would: a) increase the staff nurses’ ability to recognize workplace incivility, b) reduce workplace incivility on a nursing unit, and c) increase confidence in the staff nurses’ ability to respond to workplace incivility when it occurs. The project design involved implementing a civility training program that included education about incivility through facilitated discussions, as well as teambuilding exercises and experiential learning activities involving practice in responding to incivility in a safe environment. The project was implemented in a medically-focused medical-surgical unit at a rural Kentucky hospital with a sample of nine registered nurses.  The findings of the project included no significant changes in the frequency of the nurses’ experiences with incivility in their unit.  It did result in statistically significant increases in the nurses’ self-assessed ability to recognize workplace incivility and confidence in the nurses’ ability to respond to workplace incivility when it occurs. It was concluded that implementing this type of intervention in other rural nursing settings might help nurses have greater confidence in their ability to recognize and respond to workplace incivility. Keywords:  Incivility, Nursing, Experiential learning